Conceptus metabolomic profiling reveals stage-specific phenotypes leading up to pregnancy recognition in cattle†. Issue 5 (16th February 2021) - Simintiras, Constantine A; Sánchez, José M; McDonald, Michael; O'Callaghan, Elena; Aburima, Ahmed A; Lonergan, Patrick
Abstract: Reproductive efficiency in livestock is a major driver of sustainable food production. The poorly understood process of ruminant conceptus elongation (a) prerequisites maternal pregnancy recognition, (b) is essential to successful pregnancy establishment, and (c) coincides with a period of significant conceptus mortality. Conceptuses at five key developmental stages between Days 8–16 were recovered and cultured in vitro for 6 h prior to conditioned media analysis by untargeted ultrahigh-performance liquid chromatography tandem mass spectroscopy. This global temporal biochemical interrogation of the ex situ bovine conceptus unearths two antithetical stage-specific metabolic phenotypes during tubular (metabolically retentive) vs. filamentous (secretory) development. Moreover, the retentive conceptus phenotype on Day 14 coincides with an established period of elevated metabolic density in the uterine fluid of heifers with high systemic progesterone—a model of accelerated conceptus elongation. These data, combined, suggest a metabolic mechanism underpinning conceptus elongation, thereby enhancing our understanding of the biochemical reciprocity of maternal–conceptus communication, prior to maternal pregnancy recognition. Abstract : Temporal changes in conceptus metabolism occur in the period leading to maternal pregnancy recognition.